2017
DOI: 10.1039/c6fo01669c
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effect of protease hydrolysates from ovotransferrin

Abstract: Proteins and bioactive peptides in avian egg white exert diverse biological activities. This study is designed to investigate the effect of protease hydrolysates from ovotransferrin (OVT) on bone marrow-derived dendritic cells (BMDCs) maturation. The results show that OVT-derived pepsin hydrolysate effectively inhibits lipopolysaccharide (LPS)-induced BMDCs maturation by reducing the expression levels of MHC-II, CD83, CD86 and the production of TNF-α, IL-12p70, and RANTES, but increases the production of IL-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…[ 19 ] Scientists have shown that OVT and its hydrolysates exerted an immunomodulatory effect on the maturation of dendritic cells and alleviated immune dysfunction. [ 3,20 ] Our results were in line with the previous literature suggesting the supplement of OVT might contribute to immunomodulatory function in the intestine. Moreover, OVT affected the signal transduction pathway by downregulating the sonic hedgehog (Shh) gene.…”
Section: Resultssupporting
confidence: 91%
“…[ 19 ] Scientists have shown that OVT and its hydrolysates exerted an immunomodulatory effect on the maturation of dendritic cells and alleviated immune dysfunction. [ 3,20 ] Our results were in line with the previous literature suggesting the supplement of OVT might contribute to immunomodulatory function in the intestine. Moreover, OVT affected the signal transduction pathway by downregulating the sonic hedgehog (Shh) gene.…”
Section: Resultssupporting
confidence: 91%
“…But, the biological significance of the potential immunomodulatory activity of egg white pleiotrophin in human intestine remains very speculative. In contrast, some valuable immunomodulatory activities might emerge from ovotransferrin and egg yolk vitellogenin hydrolysates [121,122] after partial degradation by digestive proteases.…”
Section: Egg Nutraceuticalsmentioning
confidence: 99%
“…In addition, several other groups have described that hydrolysates from different protein sources and different enzymatic preparations stimulate the production of cytokines in basal conditions and exert anti‐inflammatory effects in LPS‑ or ConA‐stimulated cells. The involvement of TLRs and NF κ B and a role of MAPKs has also been described. Considering that the different protein hydrolysates assayed feature unique sequences and specific structural characteristics, such as glycosylation, it is possible that a rather nonspecific mechanism of action is at play.…”
Section: Discussionmentioning
confidence: 99%